Places nearby: Facebook as a location-based social media platform. (November 2014) - Wilken, Rowan
This article examines the growing importance of Facebook as a location-focused platform. Facebook's approach has been cautious but deliberate. However, following the strategic acquisitions of location-sharing start-ups Gowalla and Glancee, Facebook has ramped up its location-based services: they launched their Nearby feature in December 2012, and adjusted their application programming interface (API) in early 2013 to enable 'seamless' location-sharing across third-party applications. These, and more recent acquisitions, are part of ambitious, longer-term moves that reposition Facebook as a local recommendation service (taking on Foursquare and Yelp), and, significantly, establish Facebook as a key local, and increasingly mobile-centred, advertising portal (taking on Google).